Effect of Oxygen and Nitrogen Sparging during Grape Fermentation on Volatile Sulphur Compounds - Lyu, X.; Araujo, L.D.; Quek, S-Y.; du Toit, W.J.; Kilmartin, P.A. (South African Journal of Enology and Viticulture, 2021)
Elemental sulphur is a common fungicide applied in vineyards before harvest, and has been found to increase the production of desirable polyfunctional mercaptans, but also H2S and unwanted reductive sulphur aroma compounds. This paper investigates the effectiveness of oxygen and nitrogen sparging, applied during fermentation, on the removal of volatile sulphur compounds in Sauvignon blanc wines. Increasing the amount of elemental sulphur added to grapes after pressing, from nil to 10 to 100 mg/L, led to an increase in the formation of 3-mercaptohexanol (3MH), of 3-mercaptohexyl acetate (3MHA) for the 10 mg/L additions only, and of some unwanted reductive compounds. Few changes were observed in the concentrations of aroma compounds when the juices were sparged with nitrogen during fermentation. Additions of oxygen during fermentation led to some decrease in the concentration of polyfunctional mercaptans for the 10 mg/L sulphur additions, but did not significantly remove reductive aroma compounds. Few differences were observed in the concentration of wine phenolics or of further wine aroma families with any of the treatments.